Operational Risk Mitigation Based on Risk Management ISO 31000:2018 – Balanced Scorecard to Increase the Income and Reputation: Case Study at IEC - Gabriella Helmi Tirayoh; Perminas Pangeran (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this study was to evaluate and mitigate operational risks in the International English Center (IEC) to enhance its income and reputation. The research employed an integrated framework that combines ISO 31000:2018 and the Balanced Scorecard. Data collection involved questionnaires and in-depth interviews with the director of the enterprise. Operational risks were assessed across seven dimensions, including internal and external fraud, employment practices and workplace safety, clients, product, and business practices, physical property damage, business disruption and system failures, and task execution and completion, as well as management processes. The research findings led to the development of a risk management plan based on the integration of ISO 31000:2018 ERM Process and the Balanced Scorecard. Based on the evaluation results, priority attention should be given to the dimensions of task execution and completion, as well as management processes, along with physical property damage. By implementing a combination of these frameworks, the enterprise can not only enhance its income and reputation but also achieve its overall objectives.